Bioenergetic programs of cancellous and cortical bone are distinct and differ with age and mechanical loading - Carolyn Chlebek; Tyler J. McNeill; Muyin Huang; Maia S. Raynor; Marjolein C. H. van der Meulen (Scientific Reports)
Abstract Mechanical loading induces bone formation in young rodents, but mechanoresponsiveness is reduced with age. Glycolytic activity and mitochondrial dysfunction increase with age and may change bone mechanotransduction. To evaluate load-induced changes to bioenergetic activity in young and adult animals, we loaded the tibia of 10-wk and 26-wk female C57BL/6J mice and examined transcriptomic responses at the mid-diaphysis, and metaphyseal cortical shell and cancellous core. Across all biological processes, oxidative phosphorylation and mitochondrial pathways were most often enriched with loading and had contrasting enrichment in young and adult animals. Following loading, young animals had temporally-coordinated differential expression of mitochondrial-associated genes, with greatest expression at the mid-diaphysis. In adults, bioenergetic gene expression was lower compared to young animals. To assess individual contributions of glycolysis and pyruvate-mediated oxidative phosphorylation to load-induced bone formation in vivo, we inhibited each pathway therapeutically and loaded the tibia of young and adult female mice for 2 weeks. In both young and adult mice, loading increased cortical bone mass, but inhibition of oxidative phosphorylation reduced cortical area and moment of inertia in both loaded and control limbs. Conversely, load-induced improvements of adult cancellous bone depended on glycolysis. In summary, mechanical loading transcriptionally activated mitochondrial pathways in an age-specific manner and bioenergetic inhibition revealed unique metabolic programs for cortical and cancellous bone.